Calibration of the roughness parameter for steady and unsteady flow models of an irrigation canal - Rabe, Alan Pielago; Loof, Rainer; Paudyal, Guna N.; Gupta, Ashim Das; Murty, V.V.N.; Government of Denmark (Bangkok : Asian Institute of Technology, 1991)
'This study is conducted for estimating the roughness coefficient for steady and unsteady flow condition s of anon prismatic irrigation canal. The research comprises of three models: (a) geometric elements calculat1 on model. (b) steady flow simulation model, and (c) unsteady flow simulation model. As a preliminary data processing a computer program using FORTRAN was developed for computing the geometric elements at any desired water stage. Cross-sectional geometry of each gaging station was measured and the variations in geometr.lc elements was incorporated in the model. The calibration procedure tries t o match the observed and simulated water level hydrographs at selected observation stations. The widely applied Double-Sweep method of linearization for solving the Saint-Venant's equations was used with the 4-point implicit finite difference scheme. In order to mat.ch the observed steady flow t o the simulated flow, different values of 'n' were computed by iterative procedure. Optimum value of the roughness coefficient was calibrated in the unsteady flow simulation model. The model developed was applied to the main reach of the Thabua Sub-Project. of the Phitsanulok Irrigation Project in Northern Thailand. Results of calibration show acceptable ranges of 'n ' values as recommended in hydraulic literature.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Irrigation canals and flumes; Hydraulics